A Conversion for Average Grain Size Based on Gamma Ray Well Log: Application in the Second Member of Xujiahe Formation of Anyue Area, Sichuan Basin - Chen, Liang; Ji, Hancheng; Qiu, Nansheng; Zhang, Liang (Frontiers in Physics, 2021)
The grain sizes of clastic rock sediments serve as important depositional indicators that are significant in sedimentology and petroleum geology studies. Generally, gamma ray, spontaneous-potential and resistivity well logs are utilized to qualitatively characterize variations in sediment grain size and determine the lithology in clastic reservoirs. However, grain size analysis of modern sedimentary samples collected from active rivers and deltas indicates that the percentage of fine depositional component has a logarithmic relationship with the average grain size in delta and river systems. Using the linear relationship to process the lithology interpretation, siltstones or mudstone is likely to be interpreted as sandstone. Therefore, a logarithmic conversion formula was built up between the gamma ray logs and measured grain size for the second member of the Xujiahe Formation of Anyue Area in the Sichuan Basin. Using the formula, the average grain size and lithology of the exploration wells were determined for the interest intervals. Furthermore, the calculated grain size gives a better understanding of the controlling factors of hydrocarbon-bearing reservoirs in the study area.